The impact of physical activity and dietary habits on glycolipemic metabolism and inflammatory markers in the elderly: a cross-sectional study - Zhang, Wentao; Zou, Limin; Chen, Jiangang (Frontiers in Nutrition, 2025)
ObjectiveMetabolic syndrome and chronic inflammation significantly impact the quality of life of the elderly. Physical activity and dietary habits are two of the most important modifiable aspects of lifestyle. Thus, this study investigated the effects of physical activity and dietary habits on relevant biomarkers in the elderly.MethodsA total of 2349 elderly participants aged 60–75 were recruited. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ) short form. Dietary habits and intakes were assessed via the Dietary Quality Questionnaire (DQQ) and 24-h recalls. Fasting blood samples were analyzed for glycolipid metabolism and inflammatory markers, such as C - reactive protein (CRP) and interleukin - 6 (IL - 6).ResultsThere was a close association between physical activity and diet. Moderate - intensity physical activity (MPA) was positively associated with the intake of dark green leafy vegetables (β = 0.174) and negatively associated with the intake of unprocessed red meat (β = −0.112) and deep - fried foods (β = −0.117). Both physical activity and diet affected biomarkers. Vigorous physical activity was positively correlated with high - density lipoprotein cholesterol (r = 0.144), while MPA was negatively correlated with blood glucose (r = −0.127) and CRP (r = −0.129). The percentage of protein intake was positively correlated with triglycerides (r = 0.118). Mediation analysis demonstrated the combined effects of physical activity and diet. The results showed that MPA significantly and negatively affected CRP levels, with the intake of dark green leafy vegetables mediating this relationship (P < 0.05). MPA also significantly and negatively affected blood glucose levels, with vitamin B12 intake mediating this relationship (P < 0.05).ConclusionThe study indicates that physical activity and diet interact with each other and jointly affect blood glucose and inflammation in the elderly. Diet mediates the effect of physical activity on biomarkers. Further longitudinal studies are needed to verify the findings of this study.